What People Feared in Soviet Times: Expression of Everyday Fears in Urban Legends and Rumors - Racėnaitė, Radvilė (Tautosakos darbai, 2022)
Александра Архипова, Анна Кирзюк. Опасные советские вещи. Городские легенды и страхи в СССР, (сер. Культура повседневности), Москва: Новое литературное обозрение, 2020, 536 p.